Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3\(x^2\).(5\(x\) + 1) + 6\(x^3\).(5\(x\) + 2) = 9\(x^3\) .(5\(x\) + 3)
15\(x^3\) + 3\(x^2\) + 30\(x^4\) + 12\(x^3\) = 45\(x^4\) + 27\(x^3\)
(15\(x^3\) + 12\(x^3\)) + 3\(x^2\) + 30\(x^4\) - 45\(x^4\) - 27\(x^3\) = 0
27\(x^3\) + 3\(x^2\) - 15\(x^4\) - 27\(x^3\) = 0
3\(x^2\) - 15\(x^4\) = 0
3\(x^2\).(1 - 5\(x^2\)) = 0
\(\left[{}\begin{matrix}x^2=0\\1-5x^2=0\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\5x^2=1\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\x=\mp\dfrac{\sqrt{5}}{5}\end{matrix}\right.\)
2: 12-10x=25-30x
=>20x=13
=>x=13/20
3: \(3\left(2x+3\right)-2\left(4x-5\right)=10x+21\)
=>6x+9-8x+10=10x+21
=>10x+21=-2x+19
=>12x=-2
=>x=-1/6
4: \(\Leftrightarrow25x-15-6x+12=11-5x\)
=>19x-3=11-5x
=>24x=14
=>x=7/12
5: \(\Leftrightarrow8-12x-5+10x=4-6x\)
=>4-6x=-2x+3
=>-4x=-1
=>x=1/4
6: \(\Leftrightarrow32x-24-6+9x=13-40x\)
=>41x-30=13-40x
=>81x=43
=>x=43/81
7: \(\Leftrightarrow10x-5+20x=5x-11\)
=>30x-5=5x-11
=>25x=-6
=>x=-6/25
1: =>25x-15-6x+12=11-5x
=>19x-3=11-5x
=>24x=14
=>x=7/12
2: =>8-12x-5+10x=4-6x
=>4-6x=-2x+3
=>-4x=-1
=>x=1/4
1) 5x + 3 = 2(x + 7)
5x + 3 = 2x + 2.7
5x + 3 = 2x + 14
5x - 2x = 14 - 3
3x = 11
x = 11/3
Vậy x = 11/3
2) 5x - 25 = 2x - 3
5x - 2x = -3 + 25
3x = 22
x = 22/3
Vậy x = 22/3
a) (x-3)100-1=0
\(\Leftrightarrow\left(x-3\right)^{100}=0+1=1\)
\(\Leftrightarrow\left(x-3\right)^{100}=1^{100}=\left(-1\right)^{100}\)
\(\Rightarrow\left[{}\begin{matrix}x-3=1\\x-3=-1\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1+3=4\\x=\left(-1\right)+3=2\end{matrix}\right.\)
Vậy: x\(\in\left\{4;2\right\}\)
b) (9-5x)2019+1=0
\(\Leftrightarrow\left(9-5x\right)^{2019}=0-1=-1=\left(-1\right)^{2019}\)
\(\Rightarrow9-5x=-1\)
\(\Leftrightarrow5x=9-\left(-1\right)=10\)
\(\Leftrightarrow x=10:5=2\)
Vậy: x=2
a. 8x+2x =25. 2 mũ 2
8x+2x=100
(8+2)x=100
10x=100
x=100:10
x=10
b.5x+2x=35
(5+2)x=35
7x=35
x=35:7
x=5
Bài 1:
1; 5\(x\) + \(x\) = 39 - 311 : 39
\(x\).(5 + 1) = 39 - 32
\(x.6\) = 39 - 9
\(x.6\) = 30
\(x\) = 30 : 6
\(x\) = 5
Vậy \(x\) = 5
2; 5\(x\) + \(x\) = 150 : 2 + 3
\(x\).(5 + 1) = 75 + 3
\(x.6\) = 78
\(x\) = 78 : 6
\(x\) = 13
Vậy \(x=13\)
nếu là dạng tìm: x. Thì nó bằng j ạ